On the connection between mode II and mode III effective thresholds in metals (Fracture and Structural Integrity, 2017)
Closure-free long cracks under the remote mode III loading grow in a more complicated way than those under the remote mode II. For bcc metals, a coplanar in-plane spreading of tongues driven by the local mode II loading components at crack-front asperities prevails while twisting of crack-front segments to mode I, often leading to factory-roof morphology, is typical for other materials. In bcc metals, therefore, the formulation of a quantitative relationship connecting effective thresholds in modes II and III demands to calculate the local mode II components of stress intensity factors at typical asperities of a crack front loaded in the remote mode III. Therefore, a numerical model of a serrated crack front was created and the results were compared with experimentally determined ratio of mode II and III effective thresholds for the ARMCO iron. Although the calculated crack-front roughness needs an experimental verification, the preliminary results indicate that the model can provide a quantitative explanation of the experimentally observed ratio of mode II and mode III effective thresholds in bcc metals.
Keywords: Modes II and III; Effective threshold; Micromechanism; Finite element method; ARMCO iron